Evolution of extreme Total Water Levels along the northern coast of the Iberian Peninsula - D. F. Rasilla Álvarez; J. C. García Codron (Natural Hazards and Earth System Sciences, 2011)
This paper assesses the evolution of storminess along the northern coast of the Iberian Peninsula through the calculation of extreme (1%) Total Water Levels (eTWL) on both observed (tide gauge and buoy data) and hindcasted (SIMAR-44) data. Those events were first identified and then characterized in terms of oceanographic parameters and atmospheric circulation features. Additionally, an analysis of the long-term trends in both types of data was performed. Most of the events correspond to a rough wave climate and moderate storm surges, linked to extratropical disturbances following a northern track. While local atmospheric conditions seem to be evolving towards lesser storminess, their impact has been balanced by the favorable exposure of the northern coast of the Iberian Peninsula to the increasing frequency and strength of distant disturbances crossing the North Atlantic. This evolution is also correctly reproduced by the simulated long-term evolution of the forcing component (meteorological sea level residuals and wave run up) of the Total Water Level values calculated from the SIMAR 44 database, since sea level residuals have been experiencing a reduction while waves are arriving with longer periods. Finally, the addition of the rate of relative sea level trend to the temporal evolution of the atmospheric forcing component of the Total Water Level values is enough to simulate more frequent and persistent eTWL.